Modeling Laterally Loaded Single Piles Accounting for Nonlinear Soil-Pile Interactions - Maryam Mardfekri; Paolo Gardoni; Jose M. Roesset (Journal of Engineering)
The nonlinear behavior of a laterally loaded monopile foundation is studied using the finite element method (FEM) to account for soil-pile interactions. Three-dimensional (3D) finite element modeling is a convenient and reliable approach to account for the continuity of the soil mass and the nonlinearity of the soil-pile interactions. Existing simple methods for predicting the deflection of laterally loaded single piles in sand and clay (e.g., beam on elastic foundation, p-y method, and SALLOP) are assessed using linear and nonlinear finite element analyses. The results indicate that for the specific case considered here the p-y method provides a reasonable accuracy, in spite of its simplicity, in predicting the lateral deflection of single piles. A simplified linear finite element (FE) analysis of piles, often used in the literature, is also investigated and the influence of accounting for the pile diameter in the simplified linear FE model is evaluated. It is shown that modeling the pile as a line with beam-column elements results in a reduced contribution of the surrounding soil to the lateral stiffness of the pile and an increase of up to 200% in the predicted maximum lateral displacement of the pile head.